2015
DOI: 10.1002/ajh.23900
|View full text |Cite
|
Sign up to set email alerts
|

Successful discontinuation of eltrombopag after complete remission in patients with primary immune thrombocytopenia

Abstract: Eltrombopag is effective and safe in immune thrombocytopenia (ITP). Some patients may sustain their platelet response when treatment is withdrawn but the frequency of this phenomenon is unknown. We retrospectively evaluated 260 adult primary ITP patients (165 women and 95 men; median age, 62 years) treated with eltrombopag after a median time from diagnosis of 24 months. Among the 201 patients who achieved a complete remission (platelet count >100 3 10 9 /l), eltrombopag was discontinued in 80 patients. Reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 22 publications
3
80
0
1
Order By: Relevance
“…One study of adult patients with chronic ITP showed that 53% of patients had a sustained remission after stopping eltrombopag at a median follow-up of 9 months. 39 Other studies of AA have also showed durable remissions after a course of treatment with eltrombopag. 46 The ITP Consortium of North America reported on the experience of children with chronic ITP who were receiving TPO-RAs, romiplostim, and eltrombopag.…”
Section: Other Indications and Future Directionsmentioning
confidence: 96%
See 1 more Smart Citation
“…One study of adult patients with chronic ITP showed that 53% of patients had a sustained remission after stopping eltrombopag at a median follow-up of 9 months. 39 Other studies of AA have also showed durable remissions after a course of treatment with eltrombopag. 46 The ITP Consortium of North America reported on the experience of children with chronic ITP who were receiving TPO-RAs, romiplostim, and eltrombopag.…”
Section: Other Indications and Future Directionsmentioning
confidence: 96%
“…At this time, it is not possible to predict which patients might experience relapse or have a sustained response after discontinuing eltrombopag treatment. 39 …”
Section: Eltrombopag Doses In Children With Itpmentioning
confidence: 99%
“…on May 9, 2018. by guest www.bloodjournal.org From able to discontinue these agents and maintain stable platelet counts. 88,89 Similar to rituximab, some of these remissions may reflect the natural history of ITP.…”
mentioning
confidence: 99%
“…Indeed, they represent 15% of treatments given during the first year following diagnosis of ITP [9]. Furthermore, this percentage will probably increase following the recent publications reporting prolonged remission after temporary use of TPO-RA in 10 to 30% of patients [10,11].…”
Section: Introductionmentioning
confidence: 92%